Chiara Lubich's Anthropological Perspective for the Third Millennium - Jesús Moran Cepedano (Nicolaus Copernicus University in Toruń, 2019)
Today, we are witnessing the wide-ranging effects of a true anthropological emergency which, at all levels, calls for a new vision of the future in order to be addressed effectively and to change from being a huge challenge to becoming a new opportunity regarding the fate of future generations. To respond adequately to this task, it is necessary on the one hand to listen to authoritative voices that can interpret our times and, on the other, to refer to some essential phases of human history that came before the present phase. In an undertaking of this kind, it is of fundamental importance to reflect on how all this research has been received and understood within the ecclesial context and what consequences it has brought to the actual self-awareness of the Church. It is in this context that the anthropological and educative approach arising from the charism of Chiara Lubich and the experience of the Focolare Movement come into play.